2022
DOI: 10.3389/fendo.2022.1067801
|View full text |Cite
|
Sign up to set email alerts
|

Association of thyroid function, within the euthyroid range, with cardiovascular risk: The EPIPorto study

Abstract: BackgroundThyroid hormones are important modulators of cardiovascular function. Both hypothyroidism and hyperthyroidism are known to contribute to an increased cardiovascular risk. It remains uncertain whether thyroid hormones level within the euthyroid range are associated with cardiometabolic risk. We aimed to evaluate the association between thyroid function levels within the euthyroid range and cardiovascular risk in a population-based cohort.MethodsEight hundred thirty-five subjects aged ≥45 years from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Patients with CAD often have thyroid dysfunction. Previous studies have found that low FT3 levels were negatively correlated with CAD and major adverse cardiovascular events ( 28 ). The TyG index has been studied as an alternative indicator of IR in many fields.…”
Section: Discussionmentioning
confidence: 98%
“…Patients with CAD often have thyroid dysfunction. Previous studies have found that low FT3 levels were negatively correlated with CAD and major adverse cardiovascular events ( 28 ). The TyG index has been studied as an alternative indicator of IR in many fields.…”
Section: Discussionmentioning
confidence: 98%
“…The time of diagnosis of hypothyroidism was 11.8 + 5.6 years. The presence of abdominal circumference was the main criterion of metabolic syndrome, followed by high total cholesterol and in third place, high body mass index levels; these metabolic alterations have been found in the population with hypothyroidism internationally (16). These values are worrisome since they indicate a high prevalence of metabolic syndrome criteria in this particular population cohort.…”
Section: Discussionmentioning
confidence: 99%